What Differentiates Chilean Niche Software Companies: Business Knowledge and Reputation - Quispe-Sanca, A (IEEE Computer Society, 2017)
Chilean small software companies suffer a high mortality rate. Focus groups with 20 entrepreneurs and project managers from such companies shed light on what makes niche software companies more likely to survive. The extensive knowledge allowed by specializing in a niche increases the odds of success. Consequently, a company s improved reputation lets it better negotiate contracts and improve its financial situation. © 1984-2012 IEEE.